Конвергентність керування інформацією - Комова, Марія (Видавництво Львівської політехніки, 2013)
The article examines the little-known problem of the collective content. Analysis is key characteristics for modern mass communication practice concepts that are associated with both categories of interdisciplinary practice.
Keywords: communication; convergence; content; knowledge; information